HUBUNGAN PENGETAHUAN WANITA USIA SUBUR TENTANG KANKER PAYUDARA DENGAN SIKAP PEMERIKSAAN PAYUDARA SENDIRI DI YOGYAKARTA - Desi Desi; Wiwin Priyantari; Dina Putri Utami Lubis (STIKES Wira Husada Yogyakarta, 2017)
Background: Breast cancer is a case of cancer that has a high incident rate, is equal to 40 per 100,000 women. Which occurred in women of fertile age (15-45 years).Research Objectives: To know the relation the knowledge women of fertile age about breast cancer with breast self examination of the attitude. Methods: This research is the quantitative survey approach and using cross sectional Analytic. This research was conducted at May until June in Prenggan Village RW 01 Kotagede Yogyakarta. Population research as many as 240 people, and sampling using cluster random sampling cluster with the total number of respondents 71 people. The instrument of the research forms a questionnaire. The data analysis of the research using chi square Correlation technique.Results: Test analysis results chi square on samples show that the value of p value 0,004 (a < 0,05) which means there is a collerationbetween fertile age women’s knowledge about breast cancer with attitude breast self examination. Conclusion: The higher a person’s level of education, better the level of knowledge and supports a positive attitude in a person. However, the better a person’s level of knowledge is not necessarily embody good behavior.